Does smoke-free legislation work for teens too? A logistic regression analysis of smoking prevalence and gender among 16 years old in Ireland, using the 1995–2015 ESPAD school surveys. Issue 8 (16th August 2020) - Li, Shasha; Keogan, Sheila; Clancy, Luke
Abstract : Objectives: To assess the role of tobacco control legislation (TCL) in youth smoking in Ireland. To examine the effects of smoke-free legislation in youth. To consider whether TCL contributed to the gender equalisation in prevalence in 16 years old seen between 2003 and 2015. Setting: Data are from the 4 yearly European School Survey Project on Alcohol and Other Drugs from 1995 to 2015. Total sample size was 12.394. A logistic regression model on grouped data was used. Dependent variable is whether a student was a smoker in last 30 days. Independent variables are time, gender and the policy indicators, workplace ban on smoking, point-of-sale (POS) display ban, the introduction of graphical images on packs and the average real price of cigarettes. Results: Smoking prevalence dropped from 41% in 1995 to 13% in 2015. The effects of policies differed between boys and girls. For girls, estimates for workplace bans, graphical images on packs and a unit real (Consumer Price Index adjusted) price increase reduced prevalence by 7.31% (95% CI 2.94% to 11.68%), 8.80% (95% CI 2.60% to 15.01%) and 5.87 (95% CI 2.96 to 8.79), respectively. The POS ban did not have a significant effect in girls. For boys, estimates for workplace bans and a unit real price increase, reduced prevalence by 8.41% (95% CI 5.16% to 11.66%) and 4.93% (95% CI 0.77% to 9.08%), respectively, POS gave an increase of 7.02% (95% CI 1.96% to 12.40%). The introduction of graphical images had an insignificant effect. Conclusions: TC legislation helps to explain the out-of-trend reduction in youth smoking prevalence. The estimated differential effects of the workplace ban, POS displays, real price changes and graphical images on packs help to explain the sharper decline in girls than boys. These findings should remind policy-makers to give increased consideration to the possible effects on young people of any legislative changes aimed at adults in TCL.